Aktivitas Antikanker dan Antioksidan Madu di Pasaran Lokal Indonesia - La Ode Sumarlin; Anna Muawanah; Prita Wardhani; . Masitoh (Institut Pertanian Bogor, 2014)
Scientists have reported that honey contains several chemicals which have the function of antibacterial, anti-inflammatory, analgesic, wound healing, anticancer, antioxidant and free radical scavenging activity. In this study focuses on exploring the honey in the local market with anticancer and antioxidant activity. Methods used include BSLT method for potential of anticancer and antioxidant to DPPH (1,1-difenil-2-pikrilhidrazin) method. In addition, using Fourier Transform Infra Red (FTIR) analysis to test the functional groups in the honey. The analysis showed that the samples of honey has potential as an anticancer and antioxidant. Prameters of LC50 values obtained by the method Brine Shrimp Lethaly Test (BSLT) the highest as anticancer found in honey from Bali with a value 1.50 ppm. While the IC50 value obtained from DPPH method showed that honey derived from Papua has the potential antioxidant with IC50 value 5453.75 ppm. The results of the FTIR analysis showed that all of samples have the same in main functional groups. These results also indicate that honey was in the local market (Indonesia) is very potential to be consumed for various purposes, mainly to improve health.